Governing globalization - Nayyar, Deepak (Oxford University Press, 2002)
It is now more than fifty years since the United Nations system and the Bretton Woods institutions were created. The world has changed since then, and so have its governance needs in terms of institutions and rules. It is time to think about the contours of institutions and governance that would meet the needs of the world economy, and also polity, at least for the first quarter of the twenty-first century. This book is the first to examine the subject in depth